1996
DOI: 10.1017/s0031182000066531
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of platyhelminth RFamide peptides on muscle-strip preparations ofFasciola hepatica(Trematoda: Digenea)

Abstract: SUMMARYThe effects of each of the known platyhelminth neuropeptides were determined on muscle-strip preparations from the liver fluke, Fasciola hepatica. The activity of synthetic replicates of the C-terminal nonapeptide of neuropeptide F (NPF9, Moniezia expansa), and the FMRFamide-related peptides (FaRPs), GNFFRFamide, RYIRFamide, GYIRFamide and YIRFamide, were examined. Muscle-strip activity was recorded from 1 mm segments of muscle prepared from 28 to 32-day-old worms, using a photo-optic transducer system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 19 publications
(23 reference statements)
2
23
0
1
Order By: Relevance
“…1) have shown the presence of cholinergic/inhibitory and aminergic/excitatory systems, consistent with those found in other trematodes examined (Humphries et al 2000). Also, exogenous application of any one of the four known flatworm FMRFamide-related peptides (FaRPs) to muscle-strip preparations of E. caproni gave results in accord with those reported for the liver fluke, Fasciola hepatica (Marks et al 1996). The order of potency of these neuropeptides on echinostome motility was: GYIRFamide (isolated from Girardia tigrina, Bdelloura candida) > RYIRFamide (Arthurdendyus triangulatus) = YIRFamide (Bdelloura candida) > GNFFRFamide (Moniezia expansa).…”
Section: Introductionsupporting
confidence: 81%
“…1) have shown the presence of cholinergic/inhibitory and aminergic/excitatory systems, consistent with those found in other trematodes examined (Humphries et al 2000). Also, exogenous application of any one of the four known flatworm FMRFamide-related peptides (FaRPs) to muscle-strip preparations of E. caproni gave results in accord with those reported for the liver fluke, Fasciola hepatica (Marks et al 1996). The order of potency of these neuropeptides on echinostome motility was: GYIRFamide (isolated from Girardia tigrina, Bdelloura candida) > RYIRFamide (Arthurdendyus triangulatus) = YIRFamide (Bdelloura candida) > GNFFRFamide (Moniezia expansa).…”
Section: Introductionsupporting
confidence: 81%
“…The total inventory of flatworm neuropeptides to date is 6. The results are in accord with those reported for other flatworms, including F. hepatica, where the same peptides as were used with E. caproni were tested on muscle-strip preparations of the worm (Marks et al, 1996). Preliminary tests in our laboratory showed that the exogenous addition of anyone of these peptides to intact specimens of E. caproni was without effect, necessitating the worms being cut just posterior to the acetabulum in order to facilitate peptide penetration.…”
Section: Actions Of Neuropeptidessupporting
confidence: 84%
“…In addition, this biogenic amine is believed to be important in maintaining neuroplasticity in invertebrates and in the generation of muscle and nerve (Mitchell et al 2001). Although still not well understood, physiological studies so far have shown FaRPs to be myoexcitatory, inducing dose-dependent contractions in vitro of isolated muscle fibres from S. mansoni (Day et al 1994) and the marine turbellarian, Bdelloura candida and muscle strips from Fasciola hepatica (Marks et al 1996;Graham et al 1997).…”
Section: Discussionmentioning
confidence: 99%